1983
DOI: 10.1901/jaba.1983.16-371
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influences on Children's Eating Behavior and Relative Weight

Abstract: We investigated the relationship between selected parent behaviors, child mealtime behavior, and infant relative weight. Subjects were 7 male and 7 female children varying in age from 12 to 30 months (mean = 23.9 months). Each subject and parents were observed during the dinnertime meal on two occasions using the BATMAN (Bob and Tom's Method of Assessing Nutrition). The children spent 58% of the mealtime eating. They spent very little time making active decisions about what and how much they ate (food requests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
157
2
6

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(172 citation statements)
references
References 14 publications
7
157
2
6
Order By: Relevance
“…In a cross-sectional study of 3-to 5-year-old children, Johnson et al 10 found that parents who reported using a high degree of control over what and how much their children ate had children who showed relatively little evidence of energy regulation. Similarly, among children who varied in age from 12 to 30 months, Klesges et al 16 found positive correlations between the children's relative weight and parental encouragement to eat.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a cross-sectional study of 3-to 5-year-old children, Johnson et al 10 found that parents who reported using a high degree of control over what and how much their children ate had children who showed relatively little evidence of energy regulation. Similarly, among children who varied in age from 12 to 30 months, Klesges et al 16 found positive correlations between the children's relative weight and parental encouragement to eat.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7] Several mechanisms have been proposed for this protective effect, including that breastfeeding may promote a balance of control in feeding across mother-infant pairs. 9,25 Experimental 9,10 and observational 16 studies suggest a role for maternal child feeding practices in shaping how much children eat and the extent to which children are responsive to internal appetite cues to control their food intake. In a cross-sectional study of 3-to 5-year-old children, Johnson et al 10 found that parents who reported using a high degree of control over what and how much their children ate had children who showed relatively little evidence of energy regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies almost uniformly report positive associations (e.g., Klesges et al, 1983), as do laboratory observations (Drucker, Hammer, Agras, & Bryson, 1999) and questionnaire studies (Spruijt-Metz et al, 2002). These studies, however, make no differentiation among prompts in terms of variation in parents' affective style and/or message content.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…108 Children with improved self-regulation may better withstand the current food-surplus environment. 111 The second potential benefit relates to taste preference. [112][113][114][115][116] Both amniotic fluid and breast milk provide flavor exposure to the fetus and infant.…”
Section: Birth To 2 Yearsmentioning
confidence: 99%